ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA RUMAH MAKAN DAPOER LIV'S DI SITUBONDO DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Harifin, Hari; Praja, Yudha; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Marketing is the beginning of a sale. In sales, performance is measured based on how many transactions were successfully closed and some value from the transaction. Judging from the timeframe, selling aims to get marketshare where Product diversity, Prouct quality and Promotion become weapons in selling. The purpose of this research is to analyze and test Analysis Factor Which Influence Buying Decision On House Eat Dapoer Liv’s in Situbondo With Interest Buy As Variable Intervening. The population in this study were consumers of the Dapoer Liv’s restaurant. The sampling technique uses random sampling technique. This data analysis and testing uses the Structural Equation Model – Partial Least Square (PLS-SEM). Based on the hypothesis test of direct influence using the Smart PLS 3.0 application, the research result show that Product diversity has a significan effect on purchasing interest. Produc quality has a positive but not significan effect on Purchasing interest. Promotion has a significant positive effect on Purchasing interest. Product diversity has a significant positive effect on Purchasing decisions. Product quality has a positive but not significant effect on purchasing decisions. Promotion have a significan positive effect on purchasing decisions. Product diversity has a positive but not significan effect on Purchasing decisions through Purchasing interest. Product quality has a positive but not significan effect on Purchasing decisions through Purchase intention. Promotion has a positive but not significant effect on Purchasing decisions thtough Puchasing interest